Governmental Factors for Household Energy Savings: Adding The Theory of Planned Behavior - Abduh, Muhammad; Budianta, Dedik; Arinafril, Arinafril; Erina, Lili (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This study aims to investigate the relationship between household energy savings behaviors and governmental factors by implementing the theory of planned behavior (TPB). This cross-sectional study used a unique dataset compiled by Statistics Indonesia: Village Potential Statistics (VPS) Year 2011 and Environmental Care Behaviour Survey (ECBS) Year 2013. Variables connected to HES were decided by applying a logistic regression model with multivariable. Manual backward stepwise regression was performed. In the model, all variables of the planned behavior theory and its addition were significantly correlated with HES besides Intention (Very sincere: OR = 1.08, 95% CI: 0.99, 1.16). After examining the extension of five government-based variables, results of this study showed that intention, perceived behavioral control, attitude, and subjective norm might become the explanation of household energy savings